2015
DOI: 10.17113/ftb.53.01.15.3754
|View full text |Cite
|
Sign up to set email alerts
|

The Culture of Pediococcus pentosaceus T1 Inhibits Listeria Proliferation in Salmon Fillets and Controls Maturation of Kimchi

Abstract: SummaryThe objective of this study is to evaluate the antilisterial eff ect of Pediococcus pentosaceus T1, which was isolated from kimchi, and to assess its potential for extending the shelf life of salmon and kimchi. Pediococcus pentosaceus T1 culture eff ectively inhibited proliferation of Listeria monocytogenes in a dose-dependent manner in a salmon-based medium. Antilisterial eff ect of the culture was stronger than that of nisin, an antibacterial peptide, as evidenced by lower minimum inhibitory concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Staphylococcus is an important pathogen that causes infection in patients with alcoholic liver cirrhosis and increases the risk of mortality[ 36 ]. According to a previous study, antimicrobial substances from P. pentosaceus are effective at inhibiting pathogenic Staphylococcus [ 37 ]. Consistent with this finding, the relative abundance of Staphylococcus was significantly decreased after P. pentosaceus supplementation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus is an important pathogen that causes infection in patients with alcoholic liver cirrhosis and increases the risk of mortality[ 36 ]. According to a previous study, antimicrobial substances from P. pentosaceus are effective at inhibiting pathogenic Staphylococcus [ 37 ]. Consistent with this finding, the relative abundance of Staphylococcus was significantly decreased after P. pentosaceus supplementation in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, P. pentosaceus acts as a food additive, providing improved flavour by elevating the concentration of short-chain fatty acids (SCFAs) [ 10 ] and the protein hydrolysis of meat [ 11 ]. Jang et al [ 12 ] found that P. pentosaceus T1 improved texture, sourness and other organoleptic senses and thus could be a starter for original kimchi. Through suppressing LAB, P. pentosaceus T1 delayed the maturation of kimchi to improve its utility.…”
Section: Evidence Of P Pentosaceus Use In Food Enmentioning
confidence: 99%
“…Several strains of P. pentosaceus have been shown to restrict the growth of Listeria spp., such as P. pentosaceus LJR1 [ 78 ] and P. pentosaceus ATCC 43,200 [ 79 ]. For instance, P. pentosaceus T1 showed better antilisterial ability in fish products than a disinfectant and nisin, which are famous for their antibacterial abilities [ 12 ]. Yuksekdag and Aslim [ 21 ] found that five strains of Pediococcus spp.…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…P. pentosaceus also belongs to the Lactobacillaceae . Its probiotic activity is documented [70] and bacteriocins produced by its strains are able to inhibit the growth of pathogens like Listeria monocytogenes [68,69]. Pediococci have been found residing in or on plants [71,87] and the occurrence of this species in phyllosphere samples of four plant species points to a wide-spread distribution with an extensive host range.…”
Section: Discussionmentioning
confidence: 99%